Studies of Indonesian Perlidae (Plecoptera), with descriptions of three new species - Stark, Bill P. (Illiesia, 2007)
Records are presented for sixteen perlid stoneflies in Indonesia including three previously unrecognized species from Kalimantan. Most records are from the islands of Sumatra, Java or Borneo, but also included are records of Neoperla nymphs from Irian Jaya Province on the island of New Guinea. Tetropina larvata Klapálek is placed as a synonym of T. fulgescens (Enderlein)and egg descriptions based on scanning electron micrographs are provided for several species.
Keywords: entomologija; Indonezija; nove vrste